Attention bias modification in drug addiction: Enhancing control of subsequent habits - Parvaz, Muhammad A. (Proc Natl Acad Sci U S A, 2021)
A relapse in addiction is often precipitated by heightened attention bias to drug-related cues, underpinned by a subcortically mediated transition to habitual/automatized responding and reduced prefrontal control. Modification of such automatized attention bias is a fundamental, albeit elusive, target for relapse reduction. Here, on a trial-by-trial basis, we used electroencephalography and eye tracking with a task that assessed, in this order, drug cue reactivity, its instructed self-regulation via reappraisal, and the immediate aftereffects on spontaneous (i.e., not instructed and automatized) attention bias. The results show that cognitive reappraisal, a facet of prefrontal control, decreased spontaneous attention bias to drug-related cues in cocaine-addicted individuals, more so in those with less frequent recent use. The results point to the mechanisms underlying the disruption of automatized maladaptive drug-related attention bias in cocaine addiction. These results pave the way for future studies to examine the role of such habit disruption in reducing compulsive drug seeking outside the controlled laboratory environment, with the ultimate goal of developing a readily deployable cognitive-behavioral and personalized intervention for drug addiction.